2020
DOI: 10.1039/d0dt01533d
|View full text |Cite
|
Sign up to set email alerts
|

Covalent post-synthetic modification of switchable iron-based coordination polymers by volatile organic compounds: a versatile strategy for selective sensor development

Abstract: A covalent post-synthetic modification is applied in one of the most relevant polymers to obtain unprecedented switchable spin crossover (SCO) materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Achieving such a description with chemical accuracy appears today as a significant challenge for ab initio methods with strong implications in future assistance and guidance of experimental efforts devoted to the (i) development and optimization of catalytic reactivity and the (ii) design of novel spin crossover (SCO) complexes. The vast majority of SCO materials, which are of great interest for applications such as molecular spintronics, molecular electronics, sensors and actuators, [9][10][11][12] are octahedrallycoordinated Fe(II)-based molecular complexes. For these complexes, the thermodynamics of the spin transition (i.e.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Achieving such a description with chemical accuracy appears today as a significant challenge for ab initio methods with strong implications in future assistance and guidance of experimental efforts devoted to the (i) development and optimization of catalytic reactivity and the (ii) design of novel spin crossover (SCO) complexes. The vast majority of SCO materials, which are of great interest for applications such as molecular spintronics, molecular electronics, sensors and actuators, [9][10][11][12] are octahedrallycoordinated Fe(II)-based molecular complexes. For these complexes, the thermodynamics of the spin transition (i.e.…”
mentioning
confidence: 99%
“…This hypothesis is supported by different results described in the literature: 1) it is well known that molecules can be inserted between 1D polymer chains; [104][105][106] 2) different examples of PSM on polymers [107,108] and on montmorillonite sheets [109] have been also reported 3) full PSM modification in Fe-triazole chains has been already reported for solid vapor reactions. [50] The study of the spin crossover properties is also in line with a complete PSM reaction. Through the Mössbauer measurements for the different samples, we observed that at 80 K the majority of the iron centers are in the LS state, in agreement with the variabletemperature magnetic measurements.…”
Section: Discussionmentioning
confidence: 80%
“…To the best of our knowledge, concerning this family of compounds, only formations of imine by PSM methodology were described in the literature. [46][47][48]50] When it was possible, we also prepared corresponding materials using the direct synthesis (DS) method in order to ease the characterization of the desired compound.…”
Section: Syntheses Of Complexesmentioning
confidence: 99%
See 2 more Smart Citations